(untitled) (LICERE - Revista do Programa de Pós-graduação Interdisciplinar em Estudos do Lazer, 2018)
The article presents the results of monitoring and evaluation of the PELC and VS programs in the period from 2013 to 2015, obtained from the Mimboé - Monitoring and Evaluation System. The findings indicate that the objectives of the programs were largely achieved, with emphasis on the provision of systematic (workshops) and unsystematic (events) activities in sports and leisure centers in the municipalities, in a diversified and participatory manner and in dialogue with the local culture. Also, more than 16 thousand social agents were qualified in face-to-face training. Among the challenges are: instability of programs, an example of this is no agreement signed in 2016; concentration of agreements in the Southeast region and in municipalities with better socioeconomic conditions; need for improvements in aspects of implementation, such as: hourly grading, social control entity, management council and municipalization of programs.